On the rate of convergence of finite-difference approximations for Bellmans equations with variable coefficients - Krylov, N.V. (Probability theory and related fields, 2000)
The estimates presented here for parabolic Bellman's equations with variable coefficients extend the ones earlier obtained for constant coefficients.